Актуальні питання управління логістичними процесами на підприємстві - Каніщев, Ігор Андрійович (Видавничий дім «Гельветика», 2024)
UKR: Стаття присвячена актуальним питанням проведення досліджень в напрямку логістики та виявлення перспективних напрямів розвитку логістичних послуг. Оскільки логістика, і логістичні послуги, є досить важливим напрямком у розвитку як економіки України, так і світу, то кількість публікацій з даної тематики невпинно зростає, що в свою чергу потребує її аналізу. Світ постійно розвивається й без запровадження сучасних технологій, та відповідати сьогоденним потребам буде надзвичайно важко, що підкреслює важливість розгляду даної теми, адже без функціонування дійсно ефективної логістичної системи неможлива робота майже жодної галузі. У статті розглянуто сучасні методи покращення логістичних потужностей та впровадження новітніх технологій задля збільшення ефективності та економічної прибутковості шляхом якомога менших матеріальних витрат не втрачаючи при цьому якість впроваджених сучасних технологій. Також дуже важливим в даній статті є й розглянуте питання того, що існуючі на теперішній час та перевірені методи конкурентоспроможної підготовки фахівців, які орієнтовані на те, аби представляти лідерство в методах управління та бути готовими до партнерської діяльності. Це єнадзвичайно цікавою методикою, тому потребує більш інтенсивного розгляду, адже, якщо послуга, яку надає підприємство конкурентоспроможна й користується попитом, то відповідно й має бути клієнтоорієнтованою, адже це сильно може підвищити дохід підприємства. Безперечно, розглянуто питання якомога швидшої доставки за найменшу ціну та зі збереженням якості, що звичайно завжди приваблювало клієнтів, особливо у наш час, коли у логістичному бізнесі надзвичайно багато конкуренції та різноманітних пропозицій. Розглянуто декілька ефективних методів підвищення якості логістичного сполучення між підприємствами та між міжнародними партнерами, адже міжнародна торгівля є надважливим фактором існування та розвитку економіки будь-якої країни світу, а якщо країна має вихід до моря, то питання міжнародної торгівлі посідає надважливе місце у розвитку та функціонуванні національної економіки держави, тому це питання надважливе та актуальне у будь-який час. Також зроблено висновки щодо актуальності та користі для запровадження на практиці результатів проведених досліджень.

ENG: The article is devoted to topical issues of conducting research in the field of logistics and identifying promising directions for the development of logistics services. Since logistics and logistics services are a rather important direction in the development of both the economy of Ukraine and the world, the number of publications on this topic is constantly growing, which in turn requires its analysis. Undoubtedly, the world is constantly developing, and without the introduction of modern technologies, it will be extremely difficult to meet today’s needs, which emphasizes the importance of considering this topic, because without the functioning of a truly effective logistics system, it is impossible to work in almost any industry. The article examines modern methods of improving logistics capacities and introducing the latest technologies to increase efficiency and economic profitability through the lowest possible material costs without losing the quality of the implemented modern technologies. Conclusions were also made regarding the relevance and usefulness of the results of the research for implementation in practice. The article is devoted to topical issues of conducting research in the field of logistics and identifying promising directions for the development of logistics services. Since logistics and logistics services are a rather important direction in the development of both the economy of Ukraine and the world, the number of publications on this topic is constantly growing, which in turn requires its analysis. The world is constantly developing and without the introduction of modern technologies, it will be extremely difficult to meet today’s needs, which emphasizes the importance of considering this topic, because without the functioning of a truly effective logistics system, it is impossible to work in almost any industry. The article examines modern methods of improving logistics capacities and introducing the latest technologies to increase efficiency and economic profitability through the lowest possible material costs without losing the quality of the implemented modern technologies. It is also very important in this article to consider the issue of the currently existing and proven methods of competitive training of specialists, which are aimed at representing leadership in management methods and being ready for partnership activities. This is an extremely interesting technique, so it needs more intensive consideration, because if the service provided by the company is competitive and in demand, then it should be customer-oriented, because this can greatly increase the company’s income. Undoubtedly, the issue of the fastest possible delivery at the lowest price and maintaining quality has been considered, which of course has always attracted customers, especially in our time, when there is an extremely large amount of competition and various offers in the logistics business. Conclusions were also made regarding the relevance and usefulness of the results of the research for implementation in practice. Several effective methods of improving the quality of logistics connections between enterprises and between international partners are considered, because international trade is an extremely important factor in the existence and development of the economy of any country in the world, and if the country has access to the sea, then the issue of international trade occupies an extremely important place in the development and functioning of the national economy of the state, therefore this issue is very important and relevant at any time.
Current Issues of Management of Logistics Processes at the Enterprise
І. Каніщев: ORCID 0009-0007-3345-1341
Keywords: логістика; поставки; ланцюг поставок; логістичні процеси; діяльність підприємства; управління; система; логістика; парадигма логістики; матеріальні, фінансові, інформаційні, сервісні потоки; logistics; supplies; supply chain; logistics processes; enterprise activity; management; system; logistics; logistics paradigm; material, financial, information, service flows; КЕкІ; SOCIAL SCIENCES::Business and economics